Source Identification of Nosocomial Outbreak of Pseudomonas aeruginosa by Pulsed Field Gel Electrophoresis Analysis - Noor, S.S.M.; Hassan, H.; Rahman, Z.A.; Mohamed, Z.; Deris, Z.Z.; Hasas, S.A.; Rahman, R.A.; Hassan, M.; King, L.T.; Lin, T.K. (2008)
Introduction: Pseudomonas aeruginosa frequently causes nosocomial outbreaks. Accurate identification of the source is very crucial to allow more targeted and cost effective infection control intervention. Objective: The objective of this study is to describe a Pseudomonas aeruginosa outbreak in a general intensive care unit of a tertiary teaching hospital in Malaysia. Methods: Pulsed field gel electrophoresis (PFGE) was carried out to the strains with the same antibiogram. Results: PFGE done confirmed that strains isolated from patients were identical with the strains isolated from fentanyl, morphine and water used for dilution of medication. Outbreak progress: The outbreak was initially thought to be associated with dialyses water as five out of seven patients had haemodialysis done within one week before the outbreak started. The outbreak was controlled within 2 weeks following several intervention measures which include cohorting of patients, work restrictions for staff, enforcements of an alcohol-based antiseptic, review of infection control policies and improvement of ICU procedures. Conclusions: We conclude that, PFGE is an important tool in outbreak investigation for a more targeted intervention. It is recommended that PFGE is done to all strains isolated during outbreak to determine the relatedness of the strains, thus more targeted and effective infection control measures can be implemented.